PELATIHAN CALISTUNG DI DESA KEDUNGDAWA DENGAN MEDIA LAPAK BACA - Agus, Agus Khaerudin; EVA LILIS SOLIHATUN; Adinda Puteri Nabilla; Al Aziz; Duriyah (IAIC (Institut Agama Islam Cirebon), 2023)
Calistung is a basic skill that must be mastered by children who have entered elementary school (SD). Therefore, learning Calistung is very important to increase the generation that is not blind to read. However, the problem in Kedungdawa Village is that some of the children are still not fluent in reading, some even cannot write and count (Calistung). This Calistung training aims to: (1) improve the community's standard of living by understanding each other, both written and oral; (2) improving the quality of human resources, reducing the level of ignorance which is the source of poverty; (3) as access to acquire knowledge in the field of technology and information. The implementation of calistung training in Kedungdawa Village, Kedawung District, Cirebon Regency is by using “lapak baca” media.